Batik Marketing Communication as Community-Based Islamic Education: Digital Storytelling and Intercultural Aesthetics in Indonesian MSMEs - Falizar Rivani; Rofiah Siddiq; Syifa Syarifah (FIKRAH, 2025)
This study explores how batik marketing communication can serve as a form of community-based Islamic education within Indonesian micro, small, and medium enterprises (MSMEs). Employing a qualitative approach, the research was conducted in Bogor, Madura, and Yogyakarta through in-depth interviews, observations, and documentation. The findings reveal that batik production operates as non-formal learning through mentoring systems that integrate technical skills with Islamic moral values such as sincerity (ikhlas), patience (sabr), and trustworthiness (amanah). Furthermore, intercultural aesthetics in batik motifs promote multicultural awareness, while digital storytelling practices transform marketing communication into a medium of cultural literacy and digital da‘wah. This study concludes that batik marketing communication represents a holistic model of community-based Islamic education that integrates cultural preservation, digital literacy, and moral formation, offering a sustainable framework for strengthening Islamic education in contemporary society. Keywords: Batik Marketing; Islamic Education; Cultural Literacy; Digital Storytelling; Intercultural Aesthetics; Community-Based Learning.